A framework for onboard assessment and monitoring of flooding risk due to open watertight doors for passenger ships. (October 2022) - Ruponen, Pekka; Montewka, Jakub; Tompuri, Markus; Manderbacka, Teemu; Hirdaris, Spyros
Highlights: Framework linking accident susceptibility and vulnerability to flooding onboard. Accident susceptibility is based on waterway, traffic and environment complexities. Vulnerability accounts for the effects of open watertight doors on damage stability. Precalculated damage stability results enable rapid flooding risk assessment onboard. Case studies demonstrate the applicability of framework for increased crew awareness. Abstract: Post-accident safety of ships is governed by damage stability, affected by watertight subdivisions which limit accidental flooding. This is important for passenger ships with watertight doors (WTDs) often fitted in the bulkheads. Awareness of the ship flooding risk due to open WTDs and the conditions under which the associated risk level changes are prerequisites for proactive risk mitigation. Accident risk is often expressed as a combination of accident likelihood and its consequences. Current solutions for flooding risk mitigation often treat these elements separately, or the adopted metrics are based on quantities not allowing proper active control of risk. In this paper an attempt is made to fill this gap by introducing a novel concept for rapidly assessing the flooding risk onboard passenger ships, accounting for the two dimensions of flooding accidents. The likelihood part is based on the complexity of surrounding traffic, operational conditions, and human reliability assessment. The consequences are based on precalculated probabilistic damage stability results of ship survivability. The presented case studies indicate that active monitoring of flooding risk can increase the crew's situational awareness of the effect of open WTDs on the flooding risk, thus positively influencing the safety culture onboard the ship.